Combating International Cyber Conflict: A Healthy Just War and International Law Analysis of NATO and Indonesian Policies - Komalasari, Rita; Mustafa, Cecep (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
This study explores the policies of the North Atlantic Treaty Organization (NATO) and Indonesia in the context of international cyber conflict, analyzing their alignment with just war theory principles and international legal norms. By applying just war theory principles and international law, this study aims to analyze the responsible conduct of states in the realm of cyber warfare, fostering a more secure and stable international environment. This study employs a qualitative analytical method, examining the policies of NATO and Indonesia through the ethical lens of just war theory and the legal perspective of international law. The principles of jus ad bellum (righteous reasons for conflict), jus in bello (ethical conduct during conflict), and international cooperation guide the analysis, providing a comprehensive framework for evaluating the policies of these entities. Adherence to righteous reasons for cyber response, ethical conduct during cyber conflict, and international legal norms are paramount in resolving conflicts arising from cyber threats. By incorporating just war theory principles into their policies, entities can demonstrate ethical responsibility, minimize unnecessary harm, and foster an environment conducive to conflict resolution. Through this approach, NATO and Indonesia, alongside the global community, can contribute to the development of a secure and stable digital landscape. This paper's novelty lies in its integrated analysis of NATO and Indonesia's policies, considering both ethical and legal dimensions through the lens of just war theory and international law.